Florestan Fernandes' rules and sociological method: a look at empirical research in Brancos e Negros em sao paulo (1959) - Pereira, Ana Lucia; Carvalho, Alonso Bezerra de [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2020)
The article presents some considerations about the care that the sociologist Florestan Fernandes dedicates to empirical research, having as object of analysis, the second edition of the work produced in partnership with Roger Bastide, Brancos e negros em Sao Paulo: ensaio sociologico sobre os aspectos da formacao, manifestacoes atuais e efeitos do preconceito de cor na sociedade paulistana, published in 1959. Describes the work from the perspective of Florestan Fernandes himself, when he assesses his relationship with Roger Bastide, in an interview granted to the Folha de Sao Paulo, in 1995, at the end of his life. It presents the methodological procedures of empirical research explained by the authors and the commitment to science and to Brazilian society. The magnitude of the work analyzed lies in the fact that it constitutes a portal for new paths that led to the consolidation of Brazilian sociology and the deconstruction of the myth of racial democracy in Brazil.
Keywords: Whites; Black; Empirical research; Racial prejudice; Brazilian sociology